Coexistence of self-reduction from Mn4+ to Mn2+ and elastico-mechanoluminescence in diphase KZn(PO3)3:Mn2+. Issue 23 (23rd May 2019) - Chen, Huimin; Wu, Liwei; Bo, Fang; Jian, Jikang; Wu, Li; Zhang, Hongwu; Zheng, Lirong; Kong, Yongfa; Zhang, Yi; Xu, Jingjun
Abstract : The structure of KZn(PO3 )3 :Mn 2+ with a large space to accommodate defects plays an important role in its self-reduction and mechanoluminescence. Abstract : Mechanoluminescence (ML) materials have attracted much attention for potential applications in many real-time nondestructive detection and anti-counterfeiting fields; however, obtaining an orange-red emission color remains a challenge. As one of the red activators, Mn 2+ has excellent optical performance. Herein, elastico-ML materials with self-reduction of Mn 4+ to Mn 2+ were developed by selecting piezoelectric hosts with flexible frames and a large defect capacity. The divalent state of Mn was demonstrated by X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), photoluminescence (PL) spectroscopy, and X-ray absorption fine structure (XAFS) spectroscopy. A tunable luminescence from red to orange was realized and a bright red light was observed under weak mechanical stimulation. The optical and structural characteristics revealed that a unit cell with a low stiffness and large space to accommodate cation defects is a fundamental factor for the ML phenomena. This study not only offers a unique insight for understanding the self-reduction and ML phenomena of Mn 2+ -doped functional materials, but also expands the applications of advanced optical functional materials in stress sensors and optical information storage.